Endovascular robotics: technical advances and future directions - Pescio, Matteo; Kundrat, Dennis; Dagnino, Giulio (Minimally invasive therapy and allied technologies, 2025)
Endovascular interventions excel in treating cardiovascular diseases in a minimally invasive manner, showing improved outcomes over open techniques. However, challenges related to precise navigation - still relying on 2D fluoroscopy - persist. This review examines the role of robotics, highlighting commercial and research platforms, while exploring emerging trends like MRI compatibility, enhanced navigation, and autonomy. MRI-compatible systems offer radiation-free 3D imaging. Human-robot interaction evolves with task-specific interfaces, while autonomy ranges from partial to full, aiding clinical operators. Challenges include complexity and cost, emphasizing compatibility and navigation advancements. Integrating MRI-compatible robots, refining human-robot interaction, and enhancing autonomy promise advancements in endovascular surgery, fueled by AI and innovative imaging.